Quantifying the effects of the break up of Pangaea on global terrestrial diversification with neutral theory - Jordan, SMR; Barraclough, TG; Rosindell, J (Royal Society, 2016)
The historic richness of most taxonomic groups increases substantially over geological time. Explanations for this fall broadly into two categories: bias in the fossil record and elevated net rates of diversification in recent periods. For example, the break up of Pangaea and isolation between continents might have increased net diversification rates. In this study, we investigate the effect on terrestrial diversification rates of the increased isolation between land masses brought about by continental drift. We use ecological neutral theory as a means to study geologically complex scenarios tractably. Our models show the effects of simulated geological events that affect all species equally, without the added complexity of further ecological processes. We find that continental drift leads to an increase in diversity only where isolation between continents leads to additional speciation through vicariance, and where higher taxa with very low global diversity are considered. We conclude that continental drift by itself is not sufficient to account for the increase in terrestrial species richness observed in the fossil record.